Avaliação das atividades antioxidantes e citotóxicas de extratos ricos em polissacarídeos extraídos das hastes de mandacaru (Cereus Jamacaru de Candolle, Cactaceae) - Morais, Daniel de Souza Cruz (2013)
The use of medicinal plants to cure and treat various diseases is a common practice in the world and in Brazil. In several regions of the Brazil´s Northeast, the cactus Cereus jamacaru, known as mandacaru, is used popularly as a treatment to many diseases, including those related to heart respiratory diseases, gastric ulcers, scurvy, and kidney diseases. However, there is a scarcity in the scientific literature that proves scientifically the popular application of this cactus. Like other plants, Cereus jamacaru synthesizes several potentially bioactive molecules, like as polysaccharides. In this work, three polysaccharides-rich aqueous extracts, MCA80, MPM and MCP60, were obtained from this plant and analyzed chemically, as well as their cytotoxic and antioxidant potential. The data showed that all extracts consist mainly of polysaccharides (89.42 to 95.76%), but also protein (> 2%) and phenolic (3 to 8.87%) contaminants were detected. All extracts are rich in galactose, glucose and mannose. In addition, glucuronic acid was found in MCA80 and MCP60. The extracts showed total antioxidant capacity ranged from 55.21 to 68.13 of ascorbic acid equivalents (AAE). Besides, they exhibited reducer power and cupric chelation in a dose-dependent manner. None of the extracts inhibited the MTT reduction in the presence of prostate tumor cells (PC-3). However, MCP60 was the most effective extract by preventing the reduction of MTT by about 80% in the presence of cells 786. Nuclear fragmentation tests showed that this extract induces cell death. The data indicated that mandacaru synthesizes bioactive polysaccharides with potential as antioxidant and antitumor agents. For future studies, it is intended to purify and characterize these polysaccharides and its antioxidant and antitumor mechanisms